Peran Penting Penasihat Hukum dalam Peradilan Pidana Untuk Pemenuhan Hak Bantuan Hukum Tersangka Atau Terdakwa - Kelvin Chandra; R. Rahaditya (UNES Law Review, 2023)
This research aims to examine the crucial role of legal advisors in criminal justice systems in ensuring the fulfillment of legal aid rights for suspects or defendants, as prescribed by Article 54 of the Indonesian Criminal Code (KUHAP). Legal advisors play a vital role in guaranteeing that suspects or defendants have access to adequate legal assistance throughout the trial proceedings. The research employs empirical normative methods, collecting data through literature reviews and analyzing relevant case studies. The findings indicate that legal advisors have a significant impact on upholding justice and safeguarding the rights of suspects or defendants. They assist in comprehending legal rights, providing suitable legal counsel, devising defense strategies, and undertaking other duties pertaining to legal aid. Effectively meeting the requirements of legal aid positively influences the quality of the judicial process and promotes justice for suspects or defendants. Consequently, the study offers recommendations to enhance the role of legal advisors and ensure the fulfillment of legal aid rights, such as increasing financial resources and support for legal aid organizations, implementing educational programs to raise public awareness, and improving accessibility to legal aid for vulnerable groups.